2010
DOI: 10.2135/cropsci2009.10.0591
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Associated with Resistance to Rice Stripe Virus and Small Brown Planthopper Infestation in Rice

Abstract: Rice stripe is a serious viral disease of japonica rice (Oryza sativa L.) cultivars in Asia. Resistance to this disease can be divided into that to rice stripe virus (RSV) and to the pest (small brown planthopper, SBPH). Here we have used a doubled‐haploid (DH) population bred from the cross Zhaiyeqing8 (ZYQ8) × Jingxi17 (JX17) and four separate inoculation methods to genetically dissect the rice stripe resistance present in ZYQ8. Two linked RSV resistance quantitative trait loci (QTLs) were located on chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…On the other hand, Zhang et al ., Duan et al and Le et al . also detected two stable QTL on chromosome 11 and 12 using different mapping populations [2527]. Comparing QTLs for SBPH resistance identified in this study with those already reported in the literature, it seems that the QTL against SBPH detected in this study are novel.…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, Zhang et al ., Duan et al and Le et al . also detected two stable QTL on chromosome 11 and 12 using different mapping populations [2527]. Comparing QTLs for SBPH resistance identified in this study with those already reported in the literature, it seems that the QTL against SBPH detected in this study are novel.…”
Section: Discussionsupporting
confidence: 75%
“…Nowadays, for controlling this disease, insecticides have been widely used to control its transmitting vector SBPH, but the effectiveness is undesirable, and simultaneously caused great harm on the environment. Therefore, identification and utilization of insect and disease resistance genes are considered to be the most effective and economical measure (Zhang et al., ). In this study, we found that a rice variety WR24 displayed high resistance to both RBSDVD and SBPH, indicating that WR24 is a valuable germplasm line for development of resistant cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Small brown planthopper transmits virus disease (such as RBSDVD and RSV) and causes a direct damage to the plant. In previous studies, more QTLs against SBPH have been mapped using several populations (Duan et al., , ; Duan, Wan et al., ; Duan, Zhang et al., ; Sun et al., ; Tuyen et al., 2012; Wang et al., ; Zhang et al., ). Compared with these QTLs, qSBPH7 WR24 on chromosome 7 was located in the same interval as qSBPH7 .…”
Section: Discussionmentioning
confidence: 99%